A Comparative Study of Indonesia’s an New Zealand’s Company Laws - Tomi Suryo Utomo (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Company law will be an important policy for both the Indonesian Government and New Zealand Government in the future. This is because that law has proven to be extremely effective in developing companies’ performance and improving the economic situation in these countries. This paper examines the similarities and differences of company laws in Indonesia and New Zealand. There are two reasons why Indonesia and New Zealand have been chosen for this paper. The first reason is that Indonesia and New Zealand reformed their company laws in the 90s. The second one is due to the similarity of the main source of company law in Indonesian and New Zealand, namely from the common law jurisdiction Finally, this paper suggests that Indonesia should learn from New Zealand’s experience which has a more comprehensive system of company law.